Desenvolvimento de aplicativo em excel/VBA para dimensionamento de válvula de controle para líquidos, gases e vapores - Marques, Jader Martins (2019)
Control valves are equipment widely used in industries in general, especially in the chemical industry (oil and petrochemical segments, pulp and paper, etc). The lack of data of thermophysical properties of the substance in the basic engineering design or new projects from existing processes hinders the correct sizing of control valves. Given this fact, a Visual Basic for Applications (VBA) programming language of Excel was proposed, able to perform estimates of properties: vapor pressure, density and viscosity for liquids, vapors and gases typically used in the industry, in the temperature and pressure of fluid in control valve inlet and, later, the flow coefficient sizing of the control valve. The proposed application has a user friendly interface and is easy to use, being a useful tool that can be used in the Academy, as well as chemical industry professionals from the fields of Instrumentation and Process Engineering. The application, called Válvula_de_Controle_v1.0, has been validated for vapor pressure, molar volume, specific volume and viscosity, as well as the flow coefficient for liquids, vapors and gases with the data reported in the technical literature. The validation results showed that the subroutines were efficiently coded for both estimation and flow coefficient calculations. From the validation, some statistical inferences were made to compare the performance of the methods of estimation of the application with respect to simple nonpolar and polar substances. The results showed that the methods used estimate, with little or no relative error in relation to the experimental data, the properties of liquids, gases and vapors.